Harnessing therapeutic potential of vitamins and microelements to mitigate testicular damage caused by drugs or chemical toxins ‒ a review - Omotoso, Dayo Rotimi; Iwasokun, Oluwaseun; Olatomide, Oluwasegun Davis; Arogundade, Tolulope Timothy (Rzeszów University Press, 2025)
Introduction and aim. Exposure to drugs and chemical toxins has been a common cause of structural and functional impairment of the male gonad (or testis), often leading to male reproductive disorder and infertility. Health concerns due to drugs or chemical-induced testicular damage have increased the exploration of potential therapeutic agents including vitamins and microelements. This review summarizes therapeutic role of vitamins and microelements against drugs or chemical toxins in preclinical studies. Material and methods. Relevant articles published on scientific databases like PubMed, Google Scholar, Scopus, and Web of Science were retrieved and critically reviewed for this study. Analysis of the literature. The mitigating effect of essential vitamins (such as vitamin B2, vitamin B9, vitamin B12, vitamin B17, vitamin C, vitamin E) and microelements (such as zinc and selenium) has been demonstrated on testicular damage caused by exposure to drugs and chemical toxins in preclinical studies and associated with their antioxidant, anti-inflammatory and anti-apoptotic properties. This was further characterized with reparation of testicular histopathology, suppression of testicular oxidative damage, improved sperm parameters, elevated testicular antioxidants and testosterone level, upregulation of steroidogenic gene, inhibition of sperm DNA damage. Conclusion. Vitamins and microelements exert therapeutic effect against drugs and chemical-induced testicular damage.
Keywords: drugs and chemical toxins; testicular damage; vitamins and microelements